Organic Values-Based Supply Chains as a Tool for Territorial Development: A Comparative Analysis of Three European Organic Regions - Stotten, Rike; Bui, Sibylle; Pugliese, Patrizia; Schermer, Markus; Lamine, Claire (The International Journal of Sociology of Agriculture and Food, 2018)
Recently established organic regions aim to be model regions of sustainability. In the frame of this article we understand organic regions as territories that aim at the sustainable management of local resources, based on the principles of organic farming and agroecology. The contribution focuses especially on the role and configurations of values-based supply chains for the territorial development of such organic regions. Three different case studies, in Italy, France and Austria, are investigated. Principles of organic farming, according to the International Federation of Organic Agriculture Movement and the concept of neo-endogenous development by Christopher Ray, serve as framework for analyses. Finally, we include values-based supply chains into the model of neo-endogenous development for two reasons: first to link values on a territorial level, and second as a tool to permanently apply those values within a region.